2006
DOI: 10.1063/1.2362623
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen atoms on Si(100)-(2×1): Imaging with scanning tunneling microscopy

Abstract: The authors use scanning tunneling microscopy to study the initial stage of oxidation for H2O exposed Si(100). Following H2O dissociation and saturation of the surface with Cl, a mild anneal allows the oxygen to insert into the Si dimer bonds. Bridge-bonded oxygen atoms appear as a dark spot in the center of the dimer. The density of these “split dimer” defects correlates with the c-type defect density on the clean surface. These results also show how to produce nearly defect-free halogen-terminated Si(100).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 24 publications
3
24
0
Order By: Relevance
“…Supporting this view, it has been shown that the thermal decomposition of H 2 O on Si͑100͒-2 ϫ 1 starts with the insertion of O atoms into the Si-Si dimer bond. 28 Although additional oxygen atoms can insert into the Si-Si backbond at higher temperatures, there is no evidence of oxygen migration beyond the second layer in the temperature range of 300-900 K. [27][28][29][37][38][39] On the other hand, complete decomposition of NH 3 on Si͑100͒-2 ϫ 1 results in N atoms residing between the third and fifth layers, [32][33][34] indicating that in this case subsurface migration is dominant. Moreover, other investigations have suggested that ͑Si͒NH 2 species undergo subsurface insertion, either preferentially or competing with surface insertion.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Supporting this view, it has been shown that the thermal decomposition of H 2 O on Si͑100͒-2 ϫ 1 starts with the insertion of O atoms into the Si-Si dimer bond. 28 Although additional oxygen atoms can insert into the Si-Si backbond at higher temperatures, there is no evidence of oxygen migration beyond the second layer in the temperature range of 300-900 K. [27][28][29][37][38][39] On the other hand, complete decomposition of NH 3 on Si͑100͒-2 ϫ 1 results in N atoms residing between the third and fifth layers, [32][33][34] indicating that in this case subsurface migration is dominant. Moreover, other investigations have suggested that ͑Si͒NH 2 species undergo subsurface insertion, either preferentially or competing with surface insertion.…”
Section: Introductionmentioning
confidence: 98%
“…26,31 Adsorption of both NH 3 and H 2 O has been studied not only to functionalize a surface but also to unveil the initial stages of surface nitridation 18,19,[32][33][34][35][36] and oxidation. [27][28][29][37][38][39] For the NH 3 / Si͑100͒ system, in particular, a previous publication extensively reviewed the literature available. 40 In the first stage of adsorbate incorporation into a Si͑100͒-2 ϫ 1 surface, the insertion can take place either into a Si-Si dimer bond or into a Si-Si backbond, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…18 The sample was then annealed at 700 K for 5 min to obtain a saturated Si͑100͒-͑2 ϫ 1͒ surface with very low defect density. 19 SSE was achieved by exposing this surface to Cl 2 at 750-825 K. The flux was varied from 3 to 40 ϫ 10 −3 ML/ s, where 1 ML corresponds to the atom density of Si͑100͒.…”
mentioning
confidence: 99%
“…Surface cleaning has been described elsewhere. 19 Starting surfaces had point defects that amounted to 0.01-0.02 monolayer ͑ML͒, primarily in the form of dimer vacancies. Once cleaned, the surfaces were flash annealed FIG.…”
Section: Methodsmentioning
confidence: 99%